ADSORPTION OF Zn AND Pb METAL IN PRINTING WASTE OF PT. GRAFIKA WANGI KALIMANTAN USING CORN COBS CHARCOAL AS ADSORBENT - Isna Syauqiah; Fajar Insan Kusuma; Mardiana Mardiana (Konversi, 2020)
Heavy metals produced from several industrial processes cause many environmental problems. Efforts made to overcome this heavy metal pollution include adsorption methods. Agricultural by-products have the potential as an adsorbent, one of which is corn cobs. In this study, corncobs were used as Pb and Zn adsorbents. The purpose of this study was to determine the effect of particle size and stirring speed in the process of Zn and Pb metal absorption using activated charcoal. Adsorption was done by mixing 100 mL waste of PT. Grafika Wangi Kalimantan with 10 grams of activated charcoal measuring 355 micron, 500 micron and 710 micron. Each mixture is stirred for 15 minutes at speeds of 30, 60, 90, and 120 rpm and then allowed to stand for 3 hours. Analysis of the absorbed Zn and Pb metal content was carried out using a spectrophotometer at adjusted wavelengths. The greater the stirring speed, and the small size of the active charcoal particle used, decrease of Zn and Pb levels is increasing due to the better absorption of adsorbate by the adsorbent. The biggest decrease in Zn and Pb levels was seen at a stirring speed of 90 rpm and the active charcoal particle size of 355 microns where the Zn and Pb parameters contained in the sample were <0.01 mg / L.